2017
DOI: 10.1097/rct.0000000000000521
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial T2 Mapping in Patients With Hypertrophic Cardiomyopathy

Abstract: T2 mapping identified myocardial injuries suggested by the laboratory data in HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…16). In that same study [161] the T 2 values were measured in the patient myocardium with visually high T 2 , which was present in 38% of the patients. For the patients without LGE in that study the myocardial T 2 value of 48.8 ± 2.4 ms was not significantly different from controls.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 92%
See 1 more Smart Citation
“…16). In that same study [161] the T 2 values were measured in the patient myocardium with visually high T 2 , which was present in 38% of the patients. For the patients without LGE in that study the myocardial T 2 value of 48.8 ± 2.4 ms was not significantly different from controls.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 92%
“…5). One study reported T 2 values in controls of 48.1 ± 3.2 ms suggesting significantly higher T 2 values in HCM patients [161] (SMD = 1.95, 95% Cl [0.93, 2.97], I 2 = N/A, P < 0.01, Fig. 16).…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…While Huan et al showed that T2 mapping could play a role in supporting the early diagnosis of HCM [ 46 ], Amano et al demonstrated that the presence of increased T2 values in HCM patients was associated with an increase in troponin T and brain natriuretic peptide levels (BNP), underlining the potential role of T2 information in recognizing more aggressive forms characterized by significant myocardial injury [ 50 ].…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…T 2 -weighted imaging in combination with double inversion-recovery black blood preparation shows myocardial edema or inflammation associated with HCM, which may be related to chest pain, syncope, or increase in troponin T. 12 , 13 , 17 , 31 Myocardial hyperintensity on the T 2 -weighted image often locates within LGE areas ( Fig. 10 ), but can locate outside LGE.…”
Section: Introductionmentioning
confidence: 99%
“… 36 T 2 mapping is useful for confirming the presence of myocardial hyperintensity on T 2 -weighted images. 17 Nonetheless, the clinical relevance of T 1 and T 2 mapping for risk stratification of HCM has not been confirmed so far.…”
Section: Introductionmentioning
confidence: 99%